Intensity Correlations in Quantum Cascade Laser Harmonic Frequency Combs. Issue 10 (2nd August 2022) - Gabbrielli, Tecla; Bruno, Natalia; Corrias, Nicola; Borri, Simone; Consolino, Luigi; Bertrand, Mathieu; Shahmohammadi, Mehran; Franckié, Martin; Beck, Mattias; Faist, Jérôme; Zavatta, Alessandro; Cappelli, Francesco; et al.
Abstract : A novel study on harmonic frequency combs emitted by quantum cascade lasers (QCLs) is presented here, demonstrating the presence of intensity correlations between twin modes characterizing the emission spectra. These originate from a four‐wave mixing process driven by the active medium's third‐order nonlinearity. The study of such correlations is essential for the engineering of a new generation of semiconductor devices with the potential of becoming integrated emitters of light with quantum properties, such as squeezing and entanglement. Starting from experimental results, the limits of state‐of‐the‐art technology are discussed as well as the possible methodologies that could lead to the detection of nonclassical phenomena, or alternatively improve the design of QCLs, in the compelling perspective of generating quantum correlations in mid‐infrared light. Abstract : Herein, the study is focused on the intensity correlation in mid‐infrared four‐wave‐mixing‐induced harmonic frequency comb emitted by quantum cascade lasers. It outlines limits and perspectives of these devices and detection systems to pave the way for future generation and detection of quantum correlations in mid‐infrared radiation.